2023
DOI: 10.1021/acs.jproteome.3c00180
|View full text |Cite
|
Sign up to set email alerts
|

Merging Full-Spectrum and Fragment Ion Intensity Predictions from Deep Learning for High-Quality Spectral Libraries

Chak Ming Jerry Chan,
Henry Lam

Abstract: Spectral libraries are useful resources in proteomic data analysis. Recent advances in deep learning allow tandem mass spectra of peptides to be predicted from their amino acid sequences. This enables predicted spectral libraries to be compiled, and searching against such libraries has been shown to improve the sensitivity in peptide identification over conventional sequence database searching. However, current prediction models lack support for longer peptides, and thus far, predicted library searching has on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…While the authors demonstrated that Mistle works well in this use case, extrapolating such a library to all possible HLA class I peptides from a canonical human proteome would require generating, storing, and handling an msp file with more than 250 GB in size, storing upwards of 150 M spectra for ∼45 M unmodified peptide sequences. This size would increase even further when considering possible PTMs ( 116 ), mutations ( 115 ), or even cryptic HLA peptides ( 32 ). Furthermore, such libraries will likely have to be generated for every mass spectrometer and various instrument settings separately in order to maintain the high specificity of the library.…”
Section: Future Perspectivementioning
confidence: 99%
“…While the authors demonstrated that Mistle works well in this use case, extrapolating such a library to all possible HLA class I peptides from a canonical human proteome would require generating, storing, and handling an msp file with more than 250 GB in size, storing upwards of 150 M spectra for ∼45 M unmodified peptide sequences. This size would increase even further when considering possible PTMs ( 116 ), mutations ( 115 ), or even cryptic HLA peptides ( 32 ). Furthermore, such libraries will likely have to be generated for every mass spectrometer and various instrument settings separately in order to maintain the high specificity of the library.…”
Section: Future Perspectivementioning
confidence: 99%